Hidden self-harm : narratives from psychotherapy - Turp, Maggie (Jessica Kingsley Publishers, 2003)
This practical and accessible book of case studies takes a new look at self-harm, focusing on the under-explored area of 'hidden' self-harming behaviour. The roots of self-care in maternal care are investigated using the method of psychoanalytic infant observation. The case studies that follow revolve around examples of low-level self-cutting, self-hitting, eating distress and 'self-harm by omission', including unconsciously invited accidents and failures to 'take care' and to seek appropriate medical care. As well as attending to self-harming symptoms, the author highlights the importance of.